Prosedur Penerjemahan Istilah Ekonomi dalam Teks Online Bloomberg: Kajian Penerjemahan Beranotasi - Sinaga, Suisan; Jayantini, I Gusti Agung Sri Rwa (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Translating economic texts is a challenge for translators because they have to understand global economic dynamics and specific terms that are frequently not understood. This study discusses the procedures applied to translate economic terms in an economic text describing Indonesian capital market. The analyzed data were English economic terms from the online media Bloomberg, "S&P 500 Suffers Worst 'Fed Day' Since January 2021: Markets Wrap" as the source text (ST) and their Indonesian translation as the target text (TT). This study aims to describe the application of translation procedures used by the first researcher as a translator, so that the approach of analysis is an annotated translation. The translation results are described and analyzed by considering the application of translation procedures which consist of direct translation consisting of borrowing, calque and literal translation, and oblique translation namely modulation, transposition, equivalence and adaptation. The findings show that through annotated translation, it can be identified that the most predominantly-applied procedure to translate economic terms is calque, which indicates the orientation towards the source language.